Respuesta :

-2y÷2=y

3×y=-18

-3        -3

y=-21

y=3 is the correct answer. First you had to remove parenthesis first. And it gave us, [tex]-3*2y=-18[/tex]. Then multiply by the numbers. And it gave us, [tex]-6y=-18[/tex]. Next, divide by -6 from both sides of equation. And it gave us, [tex]\frac{-6y}{-6}= \frac{-18}{-6}[/tex]. And finally simplify, and it gave us the answer is y=3 is the right answer. Hope this helps! And thank you for posting your question at here on brainly, and have a great day. -Charlie